Modeling and optimization : theory and applications : MOPTA, Bethlehem, PA, USA, August 2014 selected contributions /: theory and applications : MOPTA, Bethlehem, PA, USA, August 2014 selected contributions. ([2015]) - Unknown
No abstract available